Effects of Green Light on the Stress Response of Olive Flounder Paralichthys olivaceus under Clove Oil Anesthesia - Choi, Cheol Young; Song, Jin Ah; Park, Young-Su (Ocean science journal, 2021)
Clove oil (CO) is an effective anesthetic. Many hatcheries and research studies use clove oil to immobilize fish for artificial reproduction and surgery to suppress their sensory systems during invasive procedures. In this study, olive flounder Paralichthys olivaceus were exposed to two distinct CO concentrations (25 µL/L and 50 µL/L) under white fluorescent lights and green light emitting diodes (LEDs), and the effects of CO on their stress response were investigated up to 42 h after anesthesia. The stress parameters evaluated were the prepro-melanin concentrating hormone (pMCH) and corticotropin-releasing hormone (CRH) mRNA expression levels in the brain and plasma cortisol. The results showed that anesthesia was rapidly induced in fish exposed to higher anesthetic doses and white light. However, these fish took a longer time to recover when compared with fish exposed to green light. Additionally, green light initially increased the pMCH expression, before decreasing after 14 h. The CRH and cortisol levels were measured under the same parameters; these values were lower in fish exposed to green light than those exposed to white fluorescent light. Additionally, the pMCH, CRH, and cortisol levels increased when exposed to higher CO concentrations. However, the mRNA expression levels and activity showed initial peaks, followed by a decline. Our results suggest that irradiation with green light after anesthesia reduces cortisol levels (the final product of the stress index) suggesting that this is an effective procedure to quickly recover homeostasis after anesthesia-induced stress.